A glycoporphyrin story: from chemistry to PDT treatment of cancer mouse models. Issue 11 (1st June 2018) - Lupu, M.; Maillard, Ph.; Mispelter, J.; Poyer, F.; Thomas, C. D.
Abstract : Glycoporphyrin: from bench to preclinical studies on PDX xenografted on mice. Abstract : Photodynamic therapy (PDT) represents a non-toxic and non-mutagenic antitumor therapy. The photosensitizer's (PS) chemo-physical properties are essential for the therapy, being responsible for the biological effects induced in the targeted tissues. In this study, we present the synthesis and development of some glycoconjugated porphyrins based on lectin-type receptor interaction. They were tested in vitro for finally choosing the most effective chemical structure for an optimum antitumor outcome. The most effective photosensitizer is substituted by three diethylene glycol α-d -mannosyl groups. In vivo studies allow firstly the determination of some characteristics of the biological processes triggered by the initial photochemical activation. Secondly, they make it possible to improve the therapeutic protocol in the function of the structural architecture of the targeted tumor tissue.